Eugenol-DOPO: A bio-based phosphorous-containing monomer for thiol-ene photocurable thermosets - ÇAKMAKÇI, EMRAH (My University, 2023)
The adverse health and environmental effects of petroleum-based materials have become a driving force for the fabrication of bio-based monomers. In this study, we synthesized a novel bio-based reactive phosphorus-containing; eugenol-DOPO, which was prepared in one step by the reaction of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and eugenol via Atherton–Todd reaction. Moreover, a diallyl compound was also prepared by using eugenol and piperazine. All monomers were characterized by nuclear magnetic resonance (NMR), mass, and Fourier-transform infrared (FTIR) spectroscopies. Thiol-ene photocured polysulfide thermoset networks were prepared by using these newly synthesized bio-based monomers. Thermal and thermomechanical properties of the thermosets were measured. Photo-crosslinked networks displayed over 88% gel content values. The thermal stability of the networks as well as the resulting char yields were improved as the percentage of eugenol-DOPO was increased in the formulations. The presence of N and P played a synergistic effect and the limiting oxygen index (LOI) values for the thermoset materials were enhanced. We believe eugenol-DOPO is not only a good alternative monomer for the preparation of thermally stable photocurable thermosets, but it is also a suitable bio-based additive for other polymers as well. Graphical Abstract: [Figure not available: see fulltext.].
Keywords: Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Malzeme Bilimi; MÜHENDİSLİK, ÇEVRE; POLİMER BİLİMİ; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; MATERIALS SCIENCE; CHEMISTRY; ENGINEERING, ENVIRONMENTAL; POLYMER SCIENCE; MATERIALS SCIENCE, MULTIDISCIPLINARY; Çevre Mühendisliği; Fizik Bilimleri; Polimerler ve Plastikler; Malzeme Kimyası; Environmental Engineering; Physical Sciences; Polymers and Plastics; Materials Chemistry; DOPO; Eugenol; Piperazine; Thermoset; Thiol-ene